Real‐time monitoring of carbon dioxide emissions from a shallow carbon dioxide release experiment - Kim, H.J. (2021)
This study was conducted to analyze CO2 migration from a shallow CO2 release experiment using a continuous soil CO2 flux measurement system. Approximately 1.8 t CO2 was injected from 1 to 30 June 2016 through the point sources with perforated release wells laid at 2.5‐m soil depth. Using LI‐8100A instruments, CO2 concentration, CO2 flux, soil temperature, soil moisture, relative humidity, and atmospheric pressure were continuously measured every 30 min at 0, 1.5, 3.0, 4.5, and 6.0 m from the well from 29 May to 4 August 2016. Typically sensors for soil temperature and moisture were installed at 5‐cm depth, and CO2 concentration, relative humidity, and atmospheric pressure were measured at the chambers. The CO2 flux was not maximum directly above the release well. Carbon dioxide flux at 6.0 m from the well was similar to the background level. The relationship between CO2 flux and environmental factors, described using a temporal correlation analysis, indicated that CO2 flux was primarily driven by soil temperature and had the inverse correlation with relative humidity and atmospheric pressure. Heavy rainfall inhibited in‐soil CO2 migration by filling the soil pore with water. The anomalously high CO2 flux detected at 1.5 m from the well may have been caused by the associated permeability structure, in which a permeability discrepancy leads to the vertical or horizontal flow of in‐soil CO2. These findings from this shallow CO2 release experiment should be considered as basic information to characterize and model the in‐soil CO2 transport related to CO2 leakage.